Persistence of frequency in gas–liquid flows across a change in pipe diameter or orientation - Azzopardi, Barry J.; Ijioma, Amadi; Yang, Shounan; Abdulkareem, Lokman A.; Azzi, Abdelwahid; Abdulkadir, Mukhtar (Elsevier, 2014)
From a study of the characteristics of structures across a 67/38 mm sudden contraction, using air/silicone oil flows, it has been found that frequencies of the structures (mainly slugs) persist across the contraction. This is in contrast to the velocities and lengths which increase as they move into the smaller diameter pipe. These observations were found for both vertical and 5° upward orientations. A similar persistence of frequency has been found from four other sources in the literature: a vertical (gradual) contraction; a horizontal Venturi; and two cases of horizontal pipe, 90° bend and vertical riser combination. The latter were at two contrasting conditions: (i) at atmospheric pressure with air/water in small diameter (34 mm) pipes; (ii) at 20 bar in larger diameter pipes (189 mm) using nitrogen and naphtha.